2011
DOI: 10.1111/j.1526-4637.2011.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Machine Learning Theory to Predict the Need for Femoral Nerve Block Following ACL Repair

Abstract: ML classifiers may offer improved predictive capabilities when analyzing medical data sets compared with traditional statistical methodologies in predicting severe postoperative pain requiring peripheral nerve block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Our results suggest that predictive analytics techniques, such as MLCs, may offer considerable assistance as clinical decision support tools, but must be compared and validated using multiple metrics of classifier performance. The results of this study complement previous work demonstrating the potential utility of MLC to forecast the need for a postoperative rescue femoral nerve block following anterior cruciate ligament repair [22].…”
Section: Discussionsupporting
confidence: 81%
“…Our results suggest that predictive analytics techniques, such as MLCs, may offer considerable assistance as clinical decision support tools, but must be compared and validated using multiple metrics of classifier performance. The results of this study complement previous work demonstrating the potential utility of MLC to forecast the need for a postoperative rescue femoral nerve block following anterior cruciate ligament repair [22].…”
Section: Discussionsupporting
confidence: 81%
“…This algorithm also differs from standard ‘if–then’ decision trees and classification and regression trees (CART). The ADTree method has several advantages compared with these other machine learning algorithms, including: (1) several comparative studies have shown higher accuracy and versatility for ADTree than other machine learning methods [18,19]; and (2) the ADTree model structure is less complex than other methods [16], which facilitates model interpretation and reduces the need for model optimization.…”
Section: Introductionmentioning
confidence: 99%
“…SVMs have been successfully applied to many classification and function prediction tasks, in various fields including science, engineering, and social sciences . SVM‐based classification methods have also been used for surgical applications, while similar regression techniques have been used to a comparatively lesser extent in medical applications . Our analysis was performed using LibSVM (National Taiwan University, http://www.csie.ntu.edu.tw/∼cjlin/libsvm/).…”
Section: Methodsmentioning
confidence: 99%